A field methodology to evaluate Brachiaria spp. for resistance to the spittlebug, Aeneolamia varia (F.) (Homoptera: Cercopidae) - SOTELO, GUILLERMO; CARDONA, CÉSAR (Revista Colombiana de Entomología, 2001)
In the process of developing resistance of Brachiaria spp. to the spittlebug Aeneolamia varia (F.), it is very important to reconfirm under field conditions the levels of resistance detected in greenhouse tests. Working with this insect under field conditions is difficult given its aggregated, unpredictable patterns of distribution in the field. if the infestation is not uniform, resistance ratings may be erroneous and misleading, given the occurrence of escapes. The methodology proposed in this paper has been designed to obtain homogeneous, constant insect pressure under field conditions. The infestation is first established in the greenhouse and then transferred to the field using infested plants as vehicles. Plants are taken from the field and infested in the greenhouse with 10 mature eggs per plant. Two weeks later. when nymphs are well established feeding on the roots. the plants are returned to the field. The infestation is allowed to proceed and the plants are then rated for resistance some 35-40 days after infestation. Comparisons between resistance ratings under greenhouse conditions and field conditions suggest that the field methodology is reliable.